A New Awareness: Probiotic, Prebiotic and Microbiota Knowledge and Attitude of Obstetricians - Tugrul Ersak, Duygu; Kara, Ozgur; Tanacan, Atakan; Ersak, Burak; Menekse Beser, Dilek; Sahin, Dilek (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVE: In this study, we aimed to investigate the knowledge and attitudes of obstetricians about probiotics, prebiotics, and microbiota and evaluate the differences by years in the profession. STUDY DESIGN: This cross-sectional study was conducted on obstetricians working in a tertiary center. A non-validated questionnaire consisting of 18 questions was collected face-to-face. The first part of the questionnaire evaluated the sociodemographic data and the duration of the profession, the other parts assessed the knowledge of prebiotic, probiotic, and microbiota of obstetricians and their attitudes toward prescribing or suggesting these supplements. Furthermore, the obstetricians were divided into two groups: those with a profession less than <12 years and ≥12 years according to the median value of the whole study group to assess the impact of the experience. RESULTS: There was a statistically significant difference between obstetricians with a profession of < 12 years and ≥12 years in their self-knowledge assessment of probiotics, prebiotics, and microbiota. However, the correct definitions were chosen at similar rates. Only 40% of obstetricians with a <12 years of profession thought the use of probiotics during pregnancy to be safe, while more than two-thirds of the obstetricians with a profession of ≥12 years found it safe. Additionally, significant differences were found between the groups’ sources of information, and the purpose of recommendation. CONCLUSIONS: The knowledge and attitude of obstetricians towards probiotics, prebiotics, and microbiota may be affected by the duration of the profession.